Interactive lesson as the main element of the system of formation of legal education of children with intellectual disabilities (Pedagogy of Higher and Secondary Education, 2011)
The forms of organization of lesson on bases of legal knowledge’s new for auxiliary school are offered in the article.
Keywords: right; legal education; mentally backward studying; interactive lesson